Great Speeches of the 20th Century - Edited by Clark, Tom (London Preface, 2008)
"This collection represents some fo the most well-known speeches of the 20th century. Each speech has been edited to include the most memorable and noteworthy segment. This collection was designed to be used in research in schools, colleges, and universities, or simply as reference fro those who have evan a casual interest in historically important oration."--Container insert.
Keywords: Speeches, addresses